1992
DOI: 10.1007/bf00182977
|View full text |Cite
|
Sign up to set email alerts
|

High valgus tibial osteotomy for osteoarthritis of the knee

Abstract: We report a statistical analysis of the results of 65 tibial osteotomies for primary osteoarthritis of the knee followed up at 3 and 5 years. Preoperative walking ability and the severity of pain are the factors with which the long term prognosis can best be correlated. The preoperative range of motion and mild subluxation become important at 5 years, but these factors were not important at 3 years. Mild instability did not have any influence. The severity of the osteoarthritis in radiographs and the postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…They found an ideal prognostic tibiofemoral angle to be nine degrees varus or less, which led to a probability of HTO survival for 10 years of over 90 %, but reduced to 57 % for greater pre-operative deformities. Post-operative alignment was not found to be a factor in this study, in line with several other studies, that revealed the passage of time along with pre-operative deformity were stronger prognostic factors [13,41,45,91,107]. Huang et al [42] concluded that patients with pre-operative tibiofemoral varus of greater than nine degrees may be more suitable for total knee arthroplasty.…”
Section: The Search For the Ideal Corrective Anglesupporting
confidence: 87%
“…They found an ideal prognostic tibiofemoral angle to be nine degrees varus or less, which led to a probability of HTO survival for 10 years of over 90 %, but reduced to 57 % for greater pre-operative deformities. Post-operative alignment was not found to be a factor in this study, in line with several other studies, that revealed the passage of time along with pre-operative deformity were stronger prognostic factors [13,41,45,91,107]. Huang et al [42] concluded that patients with pre-operative tibiofemoral varus of greater than nine degrees may be more suitable for total knee arthroplasty.…”
Section: The Search For the Ideal Corrective Anglesupporting
confidence: 87%
“…This might indicate that the osteotomy has to be performed earlier when the varus deformation is still minimal, although Bhan et al could find no relation between short-term results and degree of correction [22]. Additionally, we could not find a relation between the mobilisation regime (weight-or non-weight bearing) and complication rate.…”
Section: Discussioncontrasting
confidence: 64%
“…Although biomechanical tests confirmed the adequacy of the fixation and load stability of the Puddu like plates with an insert and without locking head screws [9-11], some authors raised concerns with the first generation Puddu plate in clinical case series [22,26,27]. On the other hand, the biomechanical study by Stoffel et al concluded that the TomoFix plate provides superior stability in both compression and torsion compared to the Puddu Plate and that in the latter case additional fixation might be required [12].…”
Section: Discussionmentioning
confidence: 99%